Hybrid Optimization The Ten Years of CPAIOR - van Hentenryck, Pascal; Milano, Michela; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
This volume focuses on the integration of artificial intelligence and constraint programming to solve problems in operations research and combinatorial optimization. This volume collects the contributions of experts from various research areas including decision theory, systems engineering, propositional satisfiability, mathematical optimization, and artificial intelligence. These invited scholars describe and demonstrate some of the most important topics and results from the last ten years of research related to hybrid optimization. Key Features: - Includes both well established research results, and directions for future research. - Provides several solution methods for common combinatorial optimization and decision problems. - Presents both theoretical techniques and real-world applications in artificial intelligence and operations research. Hybrid Optimization can serve as a valuable resource for graduate students, researchers and practitioners studying artificial intelligence or operations research who are interested in investigating or applying constraint programming techniques.
Keywords: Mathematics; Artificial intelligence; Mathematical optimization; Operations research; Engineering; Mathematics; Optimization; Artificial Intelligence (incl. Robotics).; Operations Research, Mathematical Programming; Computational Intelligence